International Monetary Fund Annual Report 1970. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1970)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1970. The report highlights that the performance of the world economy during 1969 and early 1970 was marked by severe inflation pressures and, at the same time, by a series of developments serving to improve the adjustment of payments imbalances in several major countries and to strengthen the international monetary system. World output and trade expanded vigorously, and, in a setting of high demand pressures and rapid price increases, interest rates soared to extraordinary levels.